A novel power control framework in virtual resource environments. (2016) - Hu, Ying
Recently, resource virtualisation technology has been widely applied in high-performance data centres. However, conventional power control techniques mainly concentrate on physical server instead of virtualised resource such virtual machine (VM). In this paper, we present a novel power control framework called virtual resource power management and control (vPMC), which applies control theory to achieve tradeoffs between power consumption and application performance. Extensive experiments are conducted to investigate the effectiveness and performance of the proposed framework. The results indicate that the vPMC framework can provide effective control on both power consumption and application performance. In addition, it can also significantly reduce the energy consumption of data centres through adaptive VM migration mechanism.